2022
DOI: 10.3390/ijms23094646
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Biomimetic Hydrogels, Encapsulated with Stromal Cell-Derived Factor 1, Improve the Composition of Foetal Tissue Grafts in a Rodent Model of Parkinson’s Disease

Abstract: Clinical studies have provided evidence for dopamine (DA) cell replacement therapy in Parkinson’s Disease. However, grafts derived from foetal tissue or pluripotent stem cells (PSCs) remain heterogeneous, with a high proportion of non-dopaminergic cells, and display subthreshold reinnervation of target tissues, thereby highlighting the need to identify new strategies to improve graft outcomes. In recent work, Stromal Cell-Derived Factor-1 (SDF1), secreted from meninges, has been shown to exert many roles durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…We, and others, have demonstrated the positive beneficial effects of biomaterial-mediated neurotrophic support on transplanted primary foetal cells in parkinsonian models [9,10,[33][34][35][36], but importantly there is a deficit of data on effects on stemcell derived DAPs. Various approaches have been used including poly(lactic-co-glycolic acid) microcarriers releasing GDNF which improved the therapeutic efficacy of foetal dopaminergic transplants in parkinsonian rats [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, and others, have demonstrated the positive beneficial effects of biomaterial-mediated neurotrophic support on transplanted primary foetal cells in parkinsonian models [9,10,[33][34][35][36], but importantly there is a deficit of data on effects on stemcell derived DAPs. Various approaches have been used including poly(lactic-co-glycolic acid) microcarriers releasing GDNF which improved the therapeutic efficacy of foetal dopaminergic transplants in parkinsonian rats [34].…”
Section: Discussionmentioning
confidence: 99%
“…Other groups, including ourselves, have used hydrogels, with Wang et al [35] demonstrating the ability of a GDNF-functionalised composite poly(l-lactic acid)/xyloglucan hydrogel to enhance survival of, and striatal reinnervation from, transplanted foetal grafts in parkinsonian mice. Hydrogels made from self-assembling peptides functionalised with GDNF [36] or stomal cell factor-1 [33] have also been shown to improve the outcome of brain repair induced by primary foetal dopaminergic grafts. In our own work, we demonstrated that the reparative capacity of transplanted foetal grafts in the rat parkinsonian brain was significantly enhanced when the cells were transplanted in the same neurotrophin-loaded collagen hydrogel used in the present study [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, flow-induced hydrodynamic shear stress has also increased EMT in 2D and 3D lung-cancer models, thus, future investigations may wish to incorporate a more effective model of measuring the 3D migration of the cells, such as a modified transwell system, its development into a bioprinted system [ 60 ] or a microfluidic platform to further access cell mobility and drug effectiveness within an artificial TME [ 61 ] The precise nature of the migrating cells and the EMT such as features of the system can be further explored via the modular approach we have detailed here. For example, other proteins [ 62 , 63 ] and biopolymers [ 64 ] can be coassembled to the system, or a population of healthy cells can be cultured in 3D before the addition of a spheroid. The lung tumour model detailed within this study could be used to further explore effective treatment of lung cancer via more tumour-like conditions, drug delivery and a model of cell mobility.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). 168 170 Additionally, considering that needle trauma may occur in CRT for other CNS and non-CNS diseases, it is of significant interest to test whether T REG cell co-transplantation can similarly reduce needle trauma-induced inflammation and enhance the survival of desired therapeutic cell products in general. 171 …”
Section: Potential Strategies To Enhance Cell Survival For Successful...mentioning
confidence: 99%